Detection of Specific Antibodies to Arboviruses in Blood Sera of Persons Residing in Kindia Province, the Republic of Guinea - E. V. Naydenova; S. A. P’yankov; A. A. Kritsky; Zh. A. Kas’an; A. S. Razdorsky; A. A. Lopatin; V. A. Safronov; E. V. Chausov; A. L. Sylla; S. Boumbaly; N. Ibrachim; M. G. Diallo; et al. (Проблемы особо опасных инфекций, 2016)
The aim of the work was to detect specific antibodies to West Nile, dengue, CCHF, and chikungunya viruses in blood sera of Guinean Kindia Province residents.Materials and methods. The obtained sera were analyzed in ELISA to discover IgG antibodies to abovementioned viruses.Results and conclusions. Detected were 267 (82 %) positive samples out of 326, containing immunoglobulins of G class to these arboviruses. The obtained data provide evidence for active circulation of dengue and West Nile fevers agents in this territory. Further studies of immune strata of the population, and possible carriers and vectors of arboviruses were demonstrated to be advisable for optimization of approaches to prophylactic (anti-epidemic) measures implementation.